Knowledge, Attitude and Practice of Community Pharmacists in Relation to Dispensing Antibiotics Without Prescription in Sudan: A Cross-sectional Study - Abdelrahman Hussain M; Osman Mohamed A; Sandel Abkar A; Siddig Mohamed F; Khider Elzubair H (Dove Medical Press, 2022)
Mohamed Abdelrahman Hussain, Ahmed Osman Mohamed, Alsara Sandel Abkar, Fatima Siddig Mohamed, Hana Khider Elzubair Department of Pharmaceutical Microbiology, Faculty of Pharmacy, International University of Africa, Khartoum, SudanCorrespondence: Ahmed Osman Mohamed, Department of Pharmaceutical Microbiology, Faculty of Pharmacy, International University of Africa, P. O. Box 2469, Madani Street, Khartoum, Sudan, Email Ahmedkunna93@hotmail.comBackground: Dispensing antibiotics without prescription (DAwP) is a widespread practice, especially in developing countries, contributing to antibiotic resistance. Community pharmacists play a significant role in promoting rational use of antibiotics by refraining from DAwP, and providing drug information to patients. This study aimed to evaluate community pharmacists' knowledge, attitude and practice, and to assess the factors behind DAwP.Methods: A cross-sectional study was conducted in 2020 among random sample of community pharmacists in Sudan. Online semi-structured questionnaire was used for data collection. The association between dependent and independent variables was assessed using Chi-square test; a P-value less than 0.05 was considered significant.Results: Of the 1217 pharmacists who participated, the majority were female (n = 645, 53%). Most pharmacists have a B. Pharm degree (n = 1026, 84%) and less than 5 years' experience (n = 718, 59%). Notably, the majority of community pharmacists have good knowledge (n = 735, 61.7%), which is significantly associated with years of experience (P < 0.00). More than half (n = 623, 52.2%) of the pharmacists have above average score of practice. Nearly all the pharmacists who participated have a positive attitude in relation to DAwP (n = 1204, 98.9%). More than half of the pharmacists were DAwP for tonsillitis (n = 817, 67%), wound infection (n = 766, 62.9%), and urinary tract infection (n = 664, 54%). The leading factor behind DAwP was the low socioeconomic status of the patients (n = 624, 51%). Additionally, 47% of the pharmacists (n = 572) thought that they were knowledgeable enough to DAwP.Conclusion: Despite their positive attitude and average level of knowledge regarding DAwP, Sudanese community pharmacists frequently are DAwP for tonsillitis. Low patients' socioeconomic status was the leading factor behind DAwP. Accordingly, extensive work from health authorities to improve the accessibility and affordability of the health system as well as the development of an antibiotic stewardship program are required to diminish DAwP.Keywords: DAwP, Sudan, pharmacist practice, antimicrobial resistance